Kinerja Guru pada Sistem Belajar Work From Home Terhadap Kreativitas Mengajar dan Respon Orangtua Siswa - Neneng Agustiningsih; Nilawati (UIN Mataram, 2023)
The purpose of this study was to determine relationship between teacher performance in the work from home learning system and the relationship between teacher performance in the work from home learning system and parents' responses at PAUD Semai Harapan Bangsa Jempong Mataram. This study uses a quantitative approach with an ex post facto type, The data collection process in this study came from respondent questionnaires, from a population of 62 parents of students, and 28 samples using the random sampling technique for teachers from a population of 8 people and the same sample, namely 8 people using the saturated sampling technique at PAUD Semai Harapan Bangsa Jempong Mataram. The results of data processing using correlation analysis in obtaining the conclusion that (-0,919) < (0,337), meaning that there is no relationship between teacher performance in the work from home learning system and teacher teaching activity (-0,971) < (0,337), meaning that there is no relationship between teacher performance in the work from home learning system and the response of parents in Semai Harapan Bangsa Jempong Mataram PAUD.